Digital Communication Strategies Through GPS Technology For Monitoring Driver Performance - Apriyanti, Tri; Sidharta, Veranus (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This study explores the use of GPS-based digital communication strategies to monitor driver performance at PT Mitra Jaya Persada. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving three key informants. The findings show that the company utilizes tools such as WhatsApp, SMS, and GPS Tracker to deliver instructions and track driver locations in real time. The monitoring team plays a central role in operational coordination. Key challenges include signal disruptions and the lack of formal training for drivers. Despite these limitations, the system has proven effective in improving discipline and accountability. The study recommends strengthening digital communication infrastructure and enhancing human resource competence in logistics operations.